Manajemen Kurikulum Bahasa Arab di Madrasah: Kajian Problematika - Aulia Rahman; Wahid Murni; Nurhadi Nurhadi (Cendekia, 2024)
The curriculum is the main thing in the educational process. To maximize it, curriculum management is needed. Arabic language learning is inseparable from curriculum management. This article seeks to analyze the problems of Arabic curriculum management qualitatively descriptively with the approach of Oliva theory in education management. Data was obtained from research articles related to Arabic curriculum management which were then analyzed with inductive techniques. The results of the research found internal and external challenges in Arabic curriculum management accompanied by problems such as the scope of planning, namely the curriculum that always changes, lesson plans and curriculum systems, and lack of teacher involvement. In terms of implementation, it is the application of the curriculum by teachers and has not been responsive to learning technology. The supervisory problems found are difficulties in making students as student centers, teachers who do not participate in curriculum development, and subjects that are less adjusted for learning outcomes. Then in terms of evaluation, the problem is different assessment and scoring, not accommodating in amiyah arabic and the priority of arabic in national curriculum management. The solution offered is continuous, competent and professional improvement of curriculum management so that the curriculum designed can achieve the goal of learning Arabic more effectively and relevant to the needs of students and society. Then add innovation to the mastery of Arabic digital learning and provide time for teachers to work together in implementing the curriculum.